Pengaruh Kepemimpinan Kepala Sekolah, Budaya Sekolah dan Profesionalisme Guru terhadap Kinerja Guru SMA Negeri Kabupaten Rembang - Susanto, Aris; Juliejantiningsih, Yovitha; Maryanto, Maryanto (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This research is motivated by teachers who are required to have performance that is able to provide and realize the hopes and desires of all parties, especially the general public who trust schools and teachers in developing students. The formulation of the problem in this research is 1. Is there an influence of the principal's leadership on teacher performance in Rembang Regency State High School. 2. Is there an influence of school culture on teacher performance in Rembang Regency State High School 3. Is there an influence of teacher professionalism on teacher performance in Rembang Regency State High School 4. Is there an influence of principal leadership, school culture and teacher professionalism together on teacher performance at Rembang Regency State High School. The aim of this research is to analyze and explain: 1. The influence of the principal's leadership on the performance of Rembang Regency State High School teachers. 2. The influence of school culture on the performance of Rembang Regency State High School teachers. 3. The influence of teacher professionalism on the performance of Rembang Regency State High School teachers. 4 .The influence of principal leadership, school culture and teacher professionalism on the performance of Rembang Regency State High School teachers. The sampling technique was based on proportional random sampling with a total of 56 teachers. The approach used in this research is quantitative. with survey methods. This research is associative research with three independent variables, namely school principal leadership (X1), school culture (X2), teacher professionalism (X3) and one dependent variable, namely teacher performance (Y). The population in this study was all 566 State High School teachers in Rembang Regency. The sampling technique was based on proportional random sampling, totaling 85. The results of the research show that the principal's leadership has a significant effect on teacher performance with a score percentage of 88.37. School culture has a significant effect on teacher performance of 89.92. Teacher professionalism obtained a percentage score of 89.36 in the very high category. With this, the principal's leadership, school culture and teacher professionalism have a positive influence and have an important role in improving teacher performance at SMAN Rembang Regency